Peningkatan Motivasi Belajar PAK Melalui Penerapan Problem Based Learnig Di Fase D Kelas VII SMP Negeri 2 Amandraya - Jernih Hati Halawa; Yohanes Umbu Lede; Paulus Asriadi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The background that encourages this non-class research is the low learning motivation of grade VII students in Catholic Religion at SMP Negeri 2 Amandraya. The research that has been conducted by the author aims to determine the improvement of Catholic religious education outcomes through learning the Problem Based Learning (PBL) model in 2024/2025. This researcher uses 2 cycle stages, each of which consists of 2 meetings. The conclusion of the study is that through the Problem Based Learning (PBL) model, it can improve the learning outcomes of Catholic religious students in grade VII (Seven). The suggestion from the researcher is that through this Problem Based Learning (PBL) model, hopefully it can make a better contribution to learning in the future.